Joint source and relay design for wireless powered AF MIMO relay systems with direct link. - Li, Bin; Rong, Yue (IEEE, 2018)
In this paper, we consider a dual-hop amplify-and-forward (AF) multiple-input multiple-output (MIMO) relay system with a wireless powered relay node. In particular, the time switching (TS) protocol is applied between wireless information and energy transfer at the relay node. The direct link between the source and destination nodes is considered. We study the joint optimization of the source and relay precoding matrices and the TS factor to maximize the source-destination mutual information (MI) when a single data stream is transmitted from the source node. We derive the optimal structure of the source and relay precoding matrices, which reduces the original problem to a simpler optimization problem. The simplified problem is then solved efficiently by a two-step method. Numerical simulations show that the proposed algorithm yields a higher MI and better rate-energy tradeoff than approaches with a fixed TS factor.